Handbook of Quantitative Science and Technology Research
DOI: 10.1007/1-4020-2755-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and Technological Performance by Gender

Abstract: Abstract:The availability of sex-disaggregated data in the fields of research, technology and development is extremely important for supporting the growing political commitment to promote and monitor women participation in the different fields of S&T. During the late 1990s the European Commission identified as a priority the availability of this data. Even if scientific publications and patents are widely accepted indicators of scientific and technological performances, until now it has been impossible to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
3

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 4 publications
3
37
0
3
Order By: Relevance
“…Previous research has sought to overcome this problem by utilizing the first names of authors and inventors to sort the data by gender [NALDI & AL., 2004].…”
Section: Database #2mentioning
confidence: 99%
“…Previous research has sought to overcome this problem by utilizing the first names of authors and inventors to sort the data by gender [NALDI & AL., 2004].…”
Section: Database #2mentioning
confidence: 99%
“…Moreover, they found that "in higher education, only 15% of those at the highest academic grade (grade A) are women" (European Commission, 2006b, p. 8). 4 This list is derived from Naldi et al (2002a;2002b) (2003) emphasize differences in the academic structures in which female and male scientists are located. However, if the differences in the distribution of resources such as space, equipment, and time are taken into account, the productivity gap between men and women seems to be negligible.…”
Section: Previous Researchmentioning
confidence: 99%
“…In the past decade there has been an evident growth in the number of methodological proposals of how to measure scientific and technological achievements taking the category of gender into consideration (Whittington & Smith-Doerr, 2005;Naldi et al, 2005;Frietsch et al, 2008). Frietsch, Haller, Vrohlings and Grupp (2009) divide the studies carried out so far into the following groups of research programmes: (1) the representation of women in science and engineering using publication activity (the analysis of the number and quality of scientific and technological publications of men and women); (2) studies of the impact of an individual's own family and maternity on scientific productivity and (3) the analysis of women's scientific career paths.…”
Section: Introductionmentioning
confidence: 99%